2017
DOI: 10.1186/s40562-017-0099-y
|View full text |Cite
|
Sign up to set email alerts
|

Different depths of near-trench slips of the 1896 Sanriku and 2011 Tohoku earthquakes

Abstract: The 1896 Sanriku earthquake was a typical 'tsunami earthquake' which caused large tsunami despite its weak ground shaking. It occurred along the Japan Trench in the northern tsunami source area of the 2011 Tohoku earthquake where a delayed tsunami generation has been proposed. Hence the relation between the 1896 and 2011 tsunami sources is an important scientific as well as societal issue. The tsunami heights along the northern and central Sanriku coasts from both earthquakes were similar, but the tsunami wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…As previously outlined, many source models have been proposed for the 2011 event (e.g., Ammon et al 2011;Koper et al 2011;Fujii et al 2011;Romano et al 2012;Yokota et al 2012;Satake et al 2013); The source model of Satake et al (2013) was adopted in the present study for the simulation of the tsunami because their source model reproduces better offshore wave profiles of the tsunami. The characteristics of the other two sources have also been investigated based on observed earthquake and tsunami records (e.g., Obana et al 2017;Satake et al 2017;Okal et al 2016;Abe 1973Abe , 1978. Kanamori (1971), for example, proposed a source model of the 1933 event based on observed seismic data.…”
Section: Numerical Modeling Of Tsunami Propagation and Inundationmentioning
confidence: 99%
See 4 more Smart Citations
“…As previously outlined, many source models have been proposed for the 2011 event (e.g., Ammon et al 2011;Koper et al 2011;Fujii et al 2011;Romano et al 2012;Yokota et al 2012;Satake et al 2013); The source model of Satake et al (2013) was adopted in the present study for the simulation of the tsunami because their source model reproduces better offshore wave profiles of the tsunami. The characteristics of the other two sources have also been investigated based on observed earthquake and tsunami records (e.g., Obana et al 2017;Satake et al 2017;Okal et al 2016;Abe 1973Abe , 1978. Kanamori (1971), for example, proposed a source model of the 1933 event based on observed seismic data.…”
Section: Numerical Modeling Of Tsunami Propagation and Inundationmentioning
confidence: 99%
“…Tanioka and Seno (2001) discussed the additional sea surface deformation of the 1896 tsunami due to horizontal displacements and bathymetry, using the model proposed by Tanioka and Satake (1996a). Satake et al (2017) re-estimated the source model based on a tsunami waveform inversion technique and compared the estimated slip amounts with that of the 2011 earthquake. Although there are some uncertainties with understanding the two events, many previous studies concluded that the 1933 earthquake was an outer-rise earthquake (e.g., Okal et al 2016;Christensen and Ruff 1988) and that the 1896 earthquake was an earthquake that occurred at (or near) the plate interface of the subducting zone (e.g., Satake et al 2017;Tanioka and Satake 1996a).…”
Section: Numerical Modeling Of Tsunami Propagation and Inundationmentioning
confidence: 99%
See 3 more Smart Citations